GAMIFICATION CONCEPT OF FIVE SENSES IN LEARNING RECEPTIVE LANGUAGE SKILL IN THE GERMAN LANGUAGE EDUCATION STUDY PROGRAM - Lestuny, Caroline; Soumokil, Piet (Pattimura Excellence Journal of Language and Culture, 2023)
Fun learning has an impact on students and lecturers. To create fun learning, it is necessary to have a game concept which contributes in learning. Gamification is not a new thing in the learning process but an important part that needs to be implemented. Receptive language skill is a subject with two language skills namely reading comprehension (Lesen) and listening comprehension (Hören). The learning process that is being carried out is quite boring because of boredom and difficulties in understanding written texts and audio texts. This research was conducted with the aim of knowing the application and perceptions of students about the concept of gamification "Five Senses" its contribution in learning. The sample in this study was 12 students. The method used was descriptive qualitative with descriptive statistical data analysis techniques. The instruments used in this study were questionnaires and observation sheets. The results of the study show that students are very motivated and enthusiastic in learning with this concept. In addition, learning using this concept creates a fun learning atmosphere and students are actively involved in building communication.